A different Laser powers and their Assisted in Ceramic Veneers Removal: (An in vitro Study) - Bydaa Ahmed Abood; Abduladheem Raouf Sulaiman (University of Mosul, College of Dentistry, 2023)
Aims: To evaluate the efficiency of an Er Cr: YSGG laser in debonding of veneers made of lithium disilicate (E-max®) as measured with the shear bond strength (SBS); determine the effect of two laser powers on the SBS required to debonding veneers, and finally determining the mode of failure for all groups. Materials and methods: Thirty ceramic discs (1mm in thickness and 5mm in diameter) were prepared according to the manufacturer's instructions. The outer surfaces of enamel for thirty bovine teeth were made flat and the discs cemented onto these prepared surfaces through using luting agent (choice 2 light cure) (Bisco, Inc, Schaumburg IL, USA). Samples were stored in distilled water for 24hours, after which they were divided randomly into three equal groups (n=10) according to the laser power used as follows: Cont.: for the control group that wasn't subjected to laser irradiation; L3: For group irradiated at 3 watt (60 sec.); L5: For group irradiated at 5 watt (60 sec.). SBS was measured by Instron universal testing machine and the failure modes were evaluated by using stereomicroscope. Results: Both lasers irradiated groups (3 and 5 watts) showed significant reduction in SBS required to debonding veneers as compared to the control group (a=.000). However, there was no significant difference between the two laser powers. Conclusion: Er,Cr:YSGG could be a safe, effective, fast and harmless method for the removal of E-.max® laminate veneers, as it caused significant reduction in SBS required for debonding of cemented veneers. Since there was no significant difference between the two laser powers therefore three watts may be advocated.